Service Marketing Mix Used to Analyze Business Opportunities to Support Chinese Tourists: A case study of Satorn and Srilom Area - Aphiphattharawarodom, Khame (Journal of Humanities and Social Sciences Thonburi University, 2020)
Abstract The Objectives to 1) study the marketing mix service to analyze the business opportunities in Pubs and Restaurants 2) study the business strategies in consistency with Chinese tourists and tourism behavior 3) guidance to the business opportunities expansion with Chinese tourists in Satorn and Srilom area. Result of the research of Marketing Mix Service Used to Analyze Business Opportunities, sorted by the signification : 1) workers 2) servicing procedure 3) physical specification of restaurant and business 4) marketing support 5) pricing 6) distributive venue 7) products and services. Business strategies, illustrates that many entrepreneurs apply the dissemination strategy by focusing on the products. Guidance to business opportunity expansion in this research shows that provided the entrepreneurs in the event discovering the interest in business expansion, the consideration concerning to the Chinese language skill for communication level to workforce in the business. Keywords: Marketing mix service, tourism, Pub and Restaurant business, customer behavior, marketing strategies